Evaluation of Intensive Statins and Proprotein Convertase Subtilisin/Kexin Type 9 Inhibitors on Intracranial Artery Plaque Stability: A Prospective Single‐Arm Study - Weiqi Zeng; Feng Zhou; Hai Zhao; Yukai Wang; Jingjuan Chen; Jiancong Lu; Dezhi Zheng; Jingyun Kuang; Dahua Yuan; Jing Zhou; Changzheng Shi; Xihai Zhao; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Intracranial atherosclerotic stenosis is a leading cause of ischemic stroke and recurrent events due to plaque instability. High‐resolution magnetic resonance imaging identifies plaque enhancement as a key marker of instability. This study evaluated the efficacy of combined high‐intensity statins and proprotein convertase subtilisin/kexin type 9 inhibitors in plaque stabilization. Methods In this prospective, single‐arm study, patients with acute stroke and intracranial atherosclerotic stroke in the M1 segment of the middle cerebral artery or basilar artery were enrolled. After 24 weeks of intensive statin and evolocumab therapy, high‐resolution magnetic resonance imaging assessments of intracranial vessels were conducted at baseline and follow‐up. The primary end point was the change in stenosis degree; secondary end points included changes in plaque enhancement (contrast ratio) and plaque burden. Results Thirty‐six patients (median age, 58 years) participated. After therapy, stenosis decreased from 75.9% (interquartile range, 69.5%–84.8%) to 65.3% (interquartile range, 53.8%–75.0%; P<0.001). Contrast ratio grades and contrast volume decreased significantly (P<0.001), and lumen area increased (from 1.03 mm2 [interquartile range, 0.59–1.72 mm2] to 2.08 mm2 [interquartile range, 1.00–3.10 mm2]; P<0.001). No significant changes were observed in wall area, wall area index, or remodeling index. A notable correlation between the decrease in low‐density lipoprotein cholesterol/apolipoprotein B ratio and reduction in contrast volume was observed. Conclusions Combining proprotein convertase subtilisin/kexin type 9 inhibitors with high‐intensity statins may improve plaque stability and reduce lumen stenosis in patients with intracranial atherosclerotic stenosis. Larger randomized controlled trials are needed to confirm these findings. Registration URL: https://www.chictr.org.cn; Unique identifier: ChiCTR2200058029.